CRITICAL ANALYSIS OF AL-QUR’AN INTERPRETATION OF RELATIONSHIP AND MANAGEMENT OF FAMILY EDUCATION - Rahman, Fawait Syaiful (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2022)
Abstrak: The family is the leading force in planting primary education for children. The family’s position is very strategic in terms of habituation of positive characters for children, especially mothers. To achieve all that, it is necessary to have ideal family education relations and management. The question is; How are family relations and management according to the Qur’an? Relationships and family education management based on a critical analysis of the exegesis of the Qur'an resulted in the conclusion that the family is the primary environment forming positive or negative values. The second responsibility of the husband is more significant in the relationship between husband and wife or parents and children. The husband is responsible for family education to give birth to a sakinah, mawaddah, wa rahmah family building system. Third, Family Education Management is the cooperation of family members in their respective duties and functions regarding education in the family. The conclusion was obtained using the thematic method (maudhu’i) al-Qur’an with descriptive-qualitative analysis from two primary and secondary sources.